Single Dose Bioavailability Study of Bilayer Matrix Tablets Containing Antihypertensive Agents - Veeran Gowda, K.; Ghosh, A.; Bhaumik, U.; Agarwal, S.; Senthamil Selvan, P.; Sahoo, B.K.; Nandi, U.; Pal, T.K. (Asian Journal of Chemistry, 2010)
The objective of this study was to determine the relative bioavailability of a fixed dose combination (FDC) product containing metoprolol tartrate 100 mg SR and ramipril 10 mg tablet. Two individual products containing metoprolol tartrate SR and the other containing ramipril were selected as the reference preparations as there was no single preparation containing these two drugs. The pharmacokinetics of metoprolol tartrate and ramipril individually after oral administration have been evaluated. However, there is no report available on the combined pharmacokinetics and bioavailability of this particular FDC. The study was designed as a single dose fasting, two periods, two way cross over study with two week wash out period. A validated liquid chromatographic mass spectrometry method (LCMS/MS) was used for the simultaneous determination of both the drugs in human plasma. No statistical differences were obtained between two preparations with respect to the mean pharmacokinetic parameters. The relative extent of absorption as assessed by the AUC ratio (test/reference) and Cmax, the average values were found to be within the acceptable range of 0.80-1.25. The results clearly indicated that both the preparations are bioequivalent in terms of rate and extent of drug absorption. Both the preparations were well tolerated and no adverse reactions were observed during the entire course of the study.